Media Magic Clay terhadap Kemampuan Mengenal Warna Primer dan Sekunder pada Anak Hambatan Intelektual Kelas V - Alysa Pragas Qurrota A'yun; Nostalgianti Citra Prystiananta; Rosika Novia Megaswarie (JOEAI (Journal of Education and Instruction), 2026)
This study aimed to determine the effect of magic clay on the primary and secondary color recognition abilities of fifth-grade children with intellectual disabilities at SLB-C TPA Jember. The method used was a Single Subject Research (SSR) with an A-B design. The results showed an increase in color recognition abilities after intervention using magic clay. In the baseline phase, the subjects' abilities were still in the low category, while during the intervention phase, there was a gradual and significant increase. This was demonstrated by an increase in the percentage of abilities, mean level, and low overlap values. In conclusion, magic clay is effective in improving primary and secondary color recognition abilities in fifth-grade children with intellectual disabilities at SLB-C TPA Jember.   Keywords: Intellectual Disabilities, Color Recognition Ability, Magic Clay, Single Subject Research